(3Qhfb GdJaGSjQs - (3eMeO Hf fLjH GdMUGQi HOQ GdMSjf Hf eSYhO GdHZhis ((3eUWai GHf GdSjO eMeO GdedG s)
(3ChdgG (B:s
(3bGd GdYHO GdVYja GdeaJbQ Edi Gddg GdhgGH eMeO Hf fLjH s
(3BNQgG (B:s
(3hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH hcGf GdaQGZ ef cJGHI gPG GdcJGH GdeHGQc SfI s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
Keywords: (3GdJaSjQ hYdhe GdbQBfs